2022
DOI: 10.1017/s0007114522003889
|View full text |Cite
|
Sign up to set email alerts
|

An evidence review and nutritional conceptual framework for pre-eclampsia prevention

Abstract: Pre-eclampsia is a serious complication of pregnancy, and maternal nutritional factors may play protective roles or exacerbate risk. The tendency to focus on single nutrients as a risk factor obscures the complexity of possible interactions, which may be important given the complex nature of pre-eclampsia. An evidence review was conducted to compile definite, probable, possible and indirect nutritional determinants of pre-eclampsia to map a nutritional conceptual framework for pre-eclampsia prevention. Determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 100 publications
2
14
0
Order By: Relevance
“…Long-term longitudinal studies have shown that higher ultra-processed food intake in women is associated with increased cardiovascular risk and hypertension [ 59 ], as can occur in women with a history of PE [ 60 ]. These data support the recommendations of other expert reviews and the World Health Organization regarding promoting healthy maternal diets [ 55 , 61 , 62 ].…”
Section: Evidence For the Role Of Nutritional Factors In The Pathophy...supporting
confidence: 87%
See 2 more Smart Citations
“…Long-term longitudinal studies have shown that higher ultra-processed food intake in women is associated with increased cardiovascular risk and hypertension [ 59 ], as can occur in women with a history of PE [ 60 ]. These data support the recommendations of other expert reviews and the World Health Organization regarding promoting healthy maternal diets [ 55 , 61 , 62 ].…”
Section: Evidence For the Role Of Nutritional Factors In The Pathophy...supporting
confidence: 87%
“…More recent observational and intervention studies provide contemporary evidence to support the role of nutritional factors in PE [ 54 ]. Evidence-based summaries from systematic reviews, meta-analyses, and representative PE expert groups (such as PRECISE) recommend healthy maternal dietary patterns to reduce the risk of PE [ 54 , 55 , 56 , 57 ].…”
Section: Evidence For the Role Of Nutritional Factors In The Pathophy...mentioning
confidence: 99%
See 1 more Smart Citation
“…There has been evidence of an association of vitamin D deficiency with different pregnancy-related disorders, such as hypertensive disorders of pregnancy, gestational diabetes, fetal growth restriction, and preterm birth, as well as common complications of the neonatal period [ 8 , 12 , 36 , 37 , 38 ]. Kinshella et al recently presented evidence that maternal vitamin D deficiency poses a nutritional risk factor for preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Kinshella et al recently presented evidence that maternal vitamin D deficiency poses a nutritional risk factor for preeclampsia. Vitamin D supplementation and healthy maternal diet were identified as protective nutritional factors associated with a lower risk of developing preeclampsia [ 37 ]. In line with these findings, the FEPED Study, assessing the effects of the maternal vitamin D status in the first trimester of pregnancy on the risks of preeclampsia, GDM, preterm birth, and SGA at birth, found a significantly decreased risk of preeclampsia associated with maternal serum 25(OH)D levels of ≥30 ng/mL in the first and third trimesters, while no significant linear relationship was identified for GDM, preterm birth, and SGA [ 39 ].…”
Section: Discussionmentioning
confidence: 99%